Systematic Literature Review: Analysis of Student's Critical Thinking Skills towards Chemistry Learning - Hana' Fadhilah Retiyanto; Sarmila Eka Putri; Muhammad Habib As-Shidiq; Suyanta Suyanta (Jurnal Penelitian Pendidikan IPA, 2023)
The research was conducted with the aim of describing the literature review on students' thinking skills on chemistry learning. This research was conducted using the Systematic Literature Review (SLR) method. The articles used were sourced from the Scopus database assisted by Publish or Perish (PoP) with a range of years 2013-2023. The focus of this research is problems and solutions related to critical thinking skills, especially in chemistry learning. The results showed that students' difficulties in learning chemistry led to low students' critical thinking skills. Therefore, the right approach and learning model are needed in learning chemistry